Axial compressive behavior of square ice filled steel tubular stub columns. (10th November 2018) - Wang, Yanlei; Chen, Guipeng; Wan, Baolin; Lin, Hao
Highlights: Square IFT column is proposed to combine the advantages of ice and steel tube. Influence of width-to-thickness ratio of steel tubes on square IFT is analyzed. Bearing capacity of IFT increases with the decrease of width-to-thickness ratio. Good composite action between outer steel tube and ice core is achieved. Equations for predicting bearing capacity of square IFT columns are proposed. Abstract: Concrete has many limitations in the building construction in cold areas. However, there is abundant ice in those regions. Therefore, using ice as a substitute for concrete has been explored by researchers. Inspired by the idea of square concrete filled steel tube (CFT), a new column form termed square ice filled steel tubular (IFT) column is proposed in this study. It consists of a square outer steel tube with the inner space filled with ice. A total of eighteen stub columns were made and tested under axial compression, including three circular plain ice specimens, nine square IFT specimens and six hollow square steel tubes, to demonstrate the advantages of the composite column. The width-to-thickness ( B / t ) ratio of the steel tubes varies from 39.5 to 77. The test results confirmed that the ice core is effectively confined by the steel tube, and the inward local buckling of the steel tube is suppressed by the inner ice, leading to higher strength and better ductility of the square IFT specimens compared with hollow steel tubes and plain ice columns. A simplified axial bearing capacity equation for square IFT stub columns is proposed and it provides reasonable and accurate predictions of the test results.